2020
DOI: 10.1016/j.ijscr.2020.11.053
|View full text |Cite
|
Sign up to set email alerts
|

Management of complex pelvic fracture and sacral fracture Denis type 2 using spanning unilateral fixation of L5 to S2AI screw

Abstract: Highlights Complex injury and unique anatomic relationships at the sacropelvic region. Use of modified approach to access the fracture site of the sacrum where dural tear is common. No complications after surgery. Alternative treatments for managing complex pelvic and sacral fractures Denis type 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Our review confirms the heterogeneity of the data in the existing literature in terms of surgical management for unstable lumbosacral fractures (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Our review confirms the heterogeneity of the data in the existing literature in terms of surgical management for unstable lumbosacral fractures (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27).…”
Section: Discussionsupporting
confidence: 79%
“…The 11 authors that used LP fixation ( 14 , 16 – 26 ) showed that spinopelvic fixation is a good technique for sacral fractures with lumbopelvic dissociation, as it allows immediate mobilization, as well as weight bearing in the postoperative period ( 29 ). Pain, neurological impairment and infection rates were low, and mobilization was earlier.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lumbopelvic fixation and iliosacral screws are currently popular fixation methods. However, both have their limitations and deficiencies 19–24 . Lumbopelvic fixation cannot fix the sacral fracture directly, which leads to a relatively high rate of non‐union because of the excessive motion of the sacrum and malunion caused by re‐displacement of the fracture.…”
Section: Discussionmentioning
confidence: 99%
“…However, both have their limitations and deficiencies. 19 , 20 , 21 , 22 , 23 , 24 Lumbopelvic fixation cannot fix the sacral fracture directly, which leads to a relatively high rate of non‐union because of the excessive motion of the sacrum and malunion caused by re‐displacement of the fracture. Meanwhile, iliosacral screws cannot simultaneously ensure reduction and fixation.…”
Section: Discussionmentioning
confidence: 99%